Human rights in Google and Bing image search results - Lopezosa, Carlos; Martorell, Sandra; Codina, Lluís (Revista General de Información y Documentación, 2022)
This research analyzes the search results for the term "derechos humanos" in Google Images and Bing Image aiming to inspect the kind of results which are returned and thereby to recognize what type of graphic representations affect the collective imaginary about human rights and which sources or institutions lead this task on the Internet. The methodologies used are the design of a constructed week  from the search results, the analysis of the content and an analysis of the Search Engine Optimization (SEO) actions taken by the websites of the identified search results to position themselves in Google.es, since its extrapolation to Bing is considered accepted. This study confirms that conceptual illustrations are prioritized in both search engines and that the websites of the United Nations and the University of Murcia are the ones that are best positioned on the Spanish version of the search engines.
Keywords: Human rights; Google Images; Bing Image; Search Engine optimization; SEO